THE INFLUENCE OF GUARANTEE VALUE, BUSINESS TURNOVER, BUSINESS AGE AND PROVISION OF ACCOUNTING INFORMATION ON FORMAL CREDIT ACCESS TO SMEs IN BANYUMAS DISTRICT - Alfiandita Rizka Meivita; Yusriyati Nur Farida (Bajang Institute, 2021)
One of the main problems faced by Small and Medium Enterprises (SMEs) is capital. The limited capital owned by SMEs encouraged them to obtain loans by accessing credit from financial institutions. However, not all SMEs can access credit from financial institutions because before giving credit the creditor needs to gain confidence that the prospective debtor is able to repay his credit based on 5C credit principles (character, capacity, capital, condition of economy, collateral). This study aims to determine the effect of collateral value, business turnover, business age and provision of accounting information on accessibility of formal credit. The type of research used is survey research. The population in this study are all SMEs engaged in the trade sector in Banyumas Regency. The sampling technique used is proportionate stratified sampling with a sample of 100 respondents. Data collection techniques in this study used survey techniques by distributing questionnaires to respondents. The data analysis technique in this study used multiple regression analysis assisted by SPSS software. The results of this study indicate that: (1) collateral value has a significant positive effect on access to formal credit, (2) business turnover has a significant positive effect on access to formal credit, (3) business age has no significant influence on access to formal credit, (4) information provision accounting has a significant positive effect on access to formal credit. Adjusted R Square testing results show that the effect of collateral value, business turnover, business age, and provision of accounting information on access to formal credit is 54.7% while 45.3% can be explained by other variables not examined. The implication of this research is to be able to increase access to formal credit, SMEs need to (1) own assets that can be used as collateral where the value must be greater than the amount of credit proposed, (2) improve their ability to manage businesses to obtain optimal business turnover, (3) strive to improve the provision of accounting information appropriately so that it can facilitate financial institutions to assess actual business conditions